Obstetric outcome in elderly nulliparous women: a comparative study - Raveendran, Sajeethakumari; Mohanapu, Swarnalatha; Murugaiah, Yogashalaini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Maternal age is an important determinant of pregnancy outcome and women aged 35 years and above delivering their first child are considered as at risk obstetric patients. The objective of this study was to determine and compare the obstetric outcome in nulliparous women 35 years and above with nulliparous women of age between 20 and 29 years of age and to compare the gestational age, birth weight, Apgar score and neonatal outcome in the two groups. Methods: It was a retrospective study done in a tertiary care hospital in South India. 192 elderly nulliparous women more than 35 years of age who delivered at this hospital during the study period were taken as study group and nulliparous women aged 20-29 years recorded next serially in the parturient register were taken as control. Selected maternal and perinatal sociodemographic factors and other outcome variables were extracted. The data were entered into a personal computer and analyzed. Results: Preeclampsia, GDM, fibroid complicating pregnancy, abruption, caesarean section rates (both elective and emergency), low birth weight babies and anomalous babies were significantly higher in elderly nulliparous women than the younger nulliparous controls. There was no significant difference in other maternal and perinatal outcome measures. Conclusions: The elderly nulliparous women are at increased risk of pregnancy complications. Hence, these patients require careful management in a multidisciplinary tertiary care hospital.